Exploring the impact of urban morphology on river cooling effects: A case study of the Arakawa river in Tokyo - Liang Zhang; Hasi Bagan; Chaomin Chen; Takahiro Yoshida (Ecological Indicators)
The impact of water bodies on mitigating temperature has gained growing attention due to the worsening urban heat island (UHI) phenomenon and efforts to develop mitigation strategies. However, most studies ignore the influence of the internal structure of the city on the cooling effect of the river. This research explores how urban morphology interacts with river cooling effects, centering on a 2000-meter buffer zone surrounding the Arakawa River in Tokyo. Through random forest regression models and correlation analysis, we quantified the impact of nine urban morphological features on Land Surface Temperature (LST) and their interaction with the river’s cooling effect. The findings reveal that high building density and large-volume structures near the river significantly obstruct air circulation, diminishing the river’s cooling efficiency and leading to heat accumulation. However, optimizing building heights and layouts—particularly through slender structures and reducing cluster density—can enhance air movement, thereby extending the river’s cooling effect. Additionally, increasing the diversity of green spaces not only strengthens cooling effects through evaporation but also generates multi-layered synergies in distant areas and on road surfaces, further supporting urban heat mitigation strategies. These insights offer valuable guidance for mitigating heat in riverine urban environments and provide recommendations for climate conscious urban planning focused on building form, green space distribution, and river integration.